Optimal Investment Selection with a Multitude of Projects - Cantor, David G.; Lippman, Steven A. (Econometrica, 1995)
When selecting amongst a set of investment projects, the decision-maker cannot act as if her decision is made in isolation: Each investment has an impact upon subsequent cash flows and affects with future investments will be feasible and desirable. Our model provides a dynamic context in which her investment decisions can be analyzed. Our model generalizes the multi-period investment models of Gale (1965), Lippman (1970), and Cantor and Lippman (1983), by allowing an arbitrary finite number of projects. We emphasize that neither interest rates, nor net present values, nor internal rates of return are part of our model. However, all three notions arise as a consequence of our basic assumptions. In this paper we introduce a new technique for evaluating bundles of investments, the upper envelope.